Proceedings of the Tenth International Conference on Information and Communication Technologies and Development 2019
DOI: 10.1145/3287098.3287102
|View full text |Cite
|
Sign up to set email alerts
|

99dots

Abstract: Ensuring that patients adhere to prescribed medication remains an important challenge in global health. While technology has been utilized to monitor and improve adherence, solutions to date have been too costly for large-scale deployment in developing regions. This paper describes 99DOTS, a low-cost approach for tracking adherence using a combination of paper packaging and low-end mobile phones. Every day, patients reveal an unpredictable phone number behind the pills and send a free call to that number to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In the only randomized trial of 99DOTS to date, we showed that only 52% of people with TB were enrolled on 99DOTS, and 99DOTS-based treatment supervision did not improve treatment outcomes (2). Other implementation studies have found similarly low enrollment of people with TB on 99DOTS and have reported similar treatment outcomes between routine-and 99DOTS-based treatment supervision (1)(2)(3).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In the only randomized trial of 99DOTS to date, we showed that only 52% of people with TB were enrolled on 99DOTS, and 99DOTS-based treatment supervision did not improve treatment outcomes (2). Other implementation studies have found similarly low enrollment of people with TB on 99DOTS and have reported similar treatment outcomes between routine-and 99DOTS-based treatment supervision (1)(2)(3).…”
Section: Introductionmentioning
confidence: 70%
“…99DOTS is a low-cost DAT, whereby people with TB self-report medication dosing by calling toll-free phone numbers hidden underneath pills in blister packs (1,2). 99DOTS has been deployed in some Asian and African countries, including India (1,3), Uganda (2) and Kenya (4).…”
Section: Introductionmentioning
confidence: 99%
“…Data directly related to publications, such as the country and publication year, were also gathered. Information regarding adherence monitoring technologies was extracted and organized into a table for further synthesis (Multimedia Appendix 2 [1][2][3][4][5][6][9][10][11][12][13][15][16][17][18]20,).…”
Section: Data Extraction and Information Synthesismentioning
confidence: 99%
“…Some old versions of the MEMS often require manual download of the stored patient medication adherence data from the MEMS cap into the MEMS software through a small reader device [8][9][10]27,28]. Some newer versions of electronic pill bottle technologies, such as the GlowCap and AdhereTech devices, possess the ability to wirelessly transmit patient medication adherence data, providing opportunities to assess and monitor patient medication adherence in real time [1,15,18,[29][30][31]. Electronic pill bottle technologies are commonly reported to have advantages including their discrete design and small size [10,16,32,33], objective medication adherence monitoring ability [1,8,11,14,34,35], and acceptance among patients [1,30,31].…”
Section: Electronic Pill Bottlesmentioning
confidence: 99%
See 1 more Smart Citation